MiD: Enabling Integration between Web Systems - Ibiapina, Irvayne Matheus de Sousa; Neto, Pedro de Alcântara dos Santos; Avelino, Guilherme Amaral; Britto, Ricardo de Sousa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Technological solutions are increasingly present in everyday corporate environments. These solutions assist in a variety of activities that are of paramount importance to your employees, customers and partners. However, as demands grow, the complexity of business needs increases, and as a result, technology systems need to evolve to maintain the standard of service quality. In this sense, the integration between systems is an alternative to help in this evolutionary scenario, enabling the sharing of resources between different systems, contemplating interoperability, reducing unwanted redundancies and eliminating bottlenecks and incompatibilities. However, despite the advantages and benefits, there are some inherent difficulties to achieve integration, which are: the effort spent on development, the integration process with Legacy Systems, the risks associated with software modifications and the integration with software developed by third parties. Because of this, we propose an approach and a tool, called MiD, to overcome such difficulties inherent in building Web Services. MiD simplifies the development of Web Services for integration between Web systems, enabling integration without the need for access to target system source code and low cost development and maintenance. An evaluation was performed to verify the advantages of using MiD in a real integration project. Preliminary results show that for the context used in the assessment environment, MiD has the potential to reduce effort in developing Web Services for integration.